(untitled) (University of Khartoum Engineering Journal, 2022)
The main objective of this paper is to address long term morphological changes for Merowe Dam Reservoir located in Sudan using River Analysis System Software (HEC-RAS 5.0.3) , The trend of three different sediment transport equations (Laursen/Copeland, Yang and Ackre/White) had been represented in terms of the volumetric bed changes. The results obtained by the model had been calibrated and validated, furthermore, Sensitivity analysis was conducted. For the model, Two different boundary conditions had been used, one is the Sediment rating curve and the other is equilibrium load. Using the predictive model concept, three bed changes scenarios were simulated, assuming repeated flows, assuming wet and dry flows, Model limitations were considered and further recommendations were highlighted.